Analisis Penyelesaian Sengketa Konsumen Melalui Arbitrase - Alisyah Early Fajrin; Sjaifurrachman Sjaifurrachman (Jurnal Analisis Hukum, 2022)
Consumer disputes are disputes that occur between consumers and business actors in buying and selling transactions. The government issued the Consumer Protection Act to provide legal protection to consumers. However, in its implementation there is also protection against arbitration decisions that should and are binding, the Consumer Law provides an opportunity for parties who object to the offer can file an objection. Therefore, this study aims to find out how to resolve consumer disputes through arbitration in laws and regulations and how to resolve conflicts in dispute resolution through arbitration. The results of the study indicate that there is a conflict of norms between the Consumer Protection Act and the Arbitration and Alternative Dispute Resolution Act regarding the nature of the arbitration award which is final and binding. A form of norm conflict is to use it as a preference.